Postponement of the opacification of lentoid bodies derived from human induced pluripotent stem cells after lanosterol treatment—the first use of the lens aging model in vitro in cataract drug screening - Zhang, Lifang; Qin, Zhenwei; Lyu, Danni; Lu, Bing; Chen, Zhijian; Fu, Qiuli; Yao, Ke (Frontiers in Pharmacology, 2022)
Purpose: Our previous study observed that human induced pluripotent stem cell (HiPSC)-derived lentoid bodies (LBs) became cloudy with extended culture time, partially mimicking the progress of human age-related cataracts (ARCs) in a dish. In the present study, lanosterol, a potential anticataract drug, was used to further verify the value of this model in drug screening for cataract treatment. Methods: Mature LBs on day 25, which were differentiated from HiPSCs using the “fried egg” method, were continually cultured and treated with either dimethyl sulfoxide (control) or lanosterol. The LBs’ shape and opacity alterations were examined using light microscopy and mean gray value evaluation. The soluble and insoluble proteins were examined through western blot combined with Coomassie blue staining. The protein aggregations were examined with immunofluorescence. Results: The mature LBs became cloudy with an extended culture time, and the opacification of the LBs was partially prevented by lanosterol treatment. There was less increase in insoluble proteins in the lanosterol-treated LBs than in the control group. There were also fewer cells containing aggregated protein (αA‐crystallin and αB‐crystallin) puncta in the lanosterol-treated LBs than in the control LBs. Conclusion: It was found that the opacification of LBs could be delayed by lanosterol treatment, which could be achieved by reducing protein aggregation, suggesting a promising HiPSC-derived drug-screening model for ARC.